Germicidal Efficiency of 272 nm LED in Relation to the Hospital Strain of Klebsiella Pneumoniae - A. S. Kamrukov; T. V. Chernenkaya; L. Yu. Volodin; S. S. Petrikov; K. A. Popugaev; V. V. Bagrov; I. V. Bukhtiyarov; E. V. Zibarev; K. A. Semenov; V. I. Krylov (Неотложная медицинская помощь, 2023)
Relevance. Currently, the use of ultraviolet (UV) radiation for the disinfection of objects and the treatment for infectious diseases is considered as a promising alternative to chemical biocides and antibiotics. Shortwave — UV-C and UV-B -light emitting diodes (LED) are a relatively new type of UV radiation sources and potentially able to meet the requirements of current medical technologies. However, their possibilities for the treatment of wounds and infectious diseases have not been practically researched to date, which determines the relevance of experiments aimed at studying the biocidal and therapeutic properties of shortwavelength UV LEDs.Purpose. OF STUDY To evaluate the bactericidal efficacy of 272 nm LED radiation against hospital strains of Klebsiella pneumoniae bacteria characterized by multidrug resistance.Materials and Methods. The studies were carried out with an experimental sample of the LED apparatus for UV irradiation. In the irradiator of the device, 5 LEDs are installed with a maximum radiation at a wavelength of 272 nm and a total electrical power of 10 watts. The UV radiation dose achieved in one irradiation session (12 seconds) at a distance of 10 cm from the irradiator was 8 mJ/cm2 . In the experiments, a hospital strain of the bacterium Klebsiella pneumoniae, isolated from the patient’s blood, was used. The strain was characterized by multidrug resistance. A daily culture suspension of K. pneumoniae with a concentration of 108 CFU/ml in a volume of 100 µl was transferred into a Petri dish with a diameter of 9 cm with meat-peptone agar and evenly distributed over a surface with a diameter of 8 cm. Petri dishes were irradiated from a distance of 10 cm from the irradiator. The change in the dose of UV irradiation from 4 to 80 mJ/cm2 was carried out by varying the exposure time. Studies were carried out in 4 repetitions at each dose. After irradiation, the experimental and control (without irradiation) Petri dishes were placed in a thermostat at 37ºC for 24 hours, then the grown colonies were counted. A total of 60 experiments were carried out.Results. As a result of the research, it was shown that the LED device based on five 272 nm diodes provides deep and prompt disinfection of the surface from hospital strains of K. pneumoniae bacteria characterized by multidrug resistance. A dose of UV radiation of 8 mJ/cm2 reduces surface contamination with K. pneumoniae bacteria by more than a million times (decontamination efficiency over 99.9999%). At doses less than 10 mJ/cm2 , the efficiency of the 272 nm LED device in terms of inactivation of K. pneumoniae bacteria is 3–4 times higher than the bactericidal efficiency of mercury lamps.Conclusion.The prospects of using UV devices based on LEDs with a maximum radiation at a wavelength of 272 nm in systems for the operational disinfection of massively contaminated surfaces, potentially including wound surfaces, have been shown.